2016
DOI: 10.1007/s10571-016-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Eleven Translocation 1 and 2 Confer Overlapping Transcriptional Programs for the Proliferation of Cultured Adult Neural Stem Cells

Abstract: Adult neurogenesis originates from neural stem cells (NSCs) in specific regions of the adult brain. The molecular mechanisms that control the self-renewal and multipotency of NSCs have not been fully elucidated. In recent years, emerging evidence has revealed that ten-eleven translocation (TET) family DNA dioxygenases TET1 and TET2 play important roles in the central nervous system. Here, I present evidence that Tet1 and Tet2 are expressed in cultured NSCs derived from adult mouse brain and play an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…It has been reported that P16 INK4a affects cell proliferation and differentiation by negatively regulating the cell cycle (32). Recently, several studies have reported that TET2 regulates cell cycle-associated proteins in neural and trophoblast stem cells (28,29). In line with these previous studies, the results of the present study suggested that the increase in P16 INK4a expression was mediated by TET2 overexpression, and si-TET2 decreased the level of P16 INK4a expression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been reported that P16 INK4a affects cell proliferation and differentiation by negatively regulating the cell cycle (32). Recently, several studies have reported that TET2 regulates cell cycle-associated proteins in neural and trophoblast stem cells (28,29). In line with these previous studies, the results of the present study suggested that the increase in P16 INK4a expression was mediated by TET2 overexpression, and si-TET2 decreased the level of P16 INK4a expression.…”
Section: Discussionsupporting
confidence: 89%
“…TET2 affects cellular proliferation and cell cycle progression in various cell lines, such as CD4 + T and Hela cells, in other conditions, including autoimmune diseases and development (5,(27)(28)(29)(30). However, the precise mechanism underlying TET2 in HaCaT cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This also implies that centrosome defects alone do not explain the slower proliferation rates and increased frequency of endoreduplication. A previous study showed that both TET1 and TET2 regulate the transcription of genes related to DNA replication (e.g., Mcm2/3/4/5/6 ) and cell-cycle progression (e.g., Ccne1 , Md2l1 , and E2f2 ) in neural stem cells ( Shimozaki, 2017 ). We also observe TET1 enrichment at cell-cycle gene loci where it likely serves to maintain an open, active chromatin configuration, akin to our findings at the Cdh1 locus.…”
Section: Discussionmentioning
confidence: 99%
“…This group of enzymes are dependent on the TCA cycle metabolite α-ketoglutarate and oxygen as essential substrates and Fe 2+ as an essential co-factor [96]. TET1 and TET2 have overlapping functions [97], a level of redundancy that reflects their biological importance, whilst TET3 is thought to be important during reprogramming within the oocyte [98] although it has recently been shown to be important at later developmental stages within the retina [99]. The TET enzymes can be regulated at multiple levels, including through DNA methylation at the TET1 and TET2 promoters [100, 101], through the action of transcription factors such as HIF1β [102], and through regulation at the mRNA and protein level [103-107].…”
Section: Epigenetic Modificationsmentioning
confidence: 99%